Internal disorder in the temporomandibular joint in young patient : Conservative Treatment vs Surgical Treatment Part 1. - Gutheil, Roberta Vasconcellos; Vannucci, Marcello (Headache Medicine, 2024)
Abstract: The patient presents with algia in the left mandible and in the ocular region, specifically at the base of the orbit. Initially, after clinical examination, the suspicion was migraine associated with bruxism with internal joint disorder. After imaging exams by tomography and magnetic resonance imaging with T1, T2, and DP contrast, it was observed that in the left temporomandibular joint, there is disc displacement without reduction, and in the right temporomandibular joint, the disc shows partial recovery. After one year of using an interocclusal device, the patient shows improvement in pain symptoms; however, the disc has only slightly improved in recovery, suggesting the possibility of future open surgery for disc repositioning through discopexy.